Analisis Pengaruh Stres Kerja dan Organizational Citizenship Behavior terhadap Kepuasan Kerja dan Dampaknya terhadap Retensi Karyawan di Ford Jakarta Pusat - Stefhani, Stefhani; Irvianti, Laksmi Sito Dwi (Bina Nusantara University, 2014)
Ford Jakarta Pusat is an authorized automotive dealer company. This study was conducted to determine how much influence of work stress and Organizational Citizenship Behaviour on job satisfaction and the impact on employee retention. There were 50 employees in Ford Jakarta Pusat used as research object. Data were obtained by spreading the questionnaire to the respondents using Cross Sectional Time Horizon. The data have been collected and processed using Path Analysis approach. According to the research result, it shows that work stress and Organizational Citizenship Behaviour have a simultaneous and significant effect on job satisfaction although work stress individually does not have a significant effect on job satisfaction. Then, work stress, Organizational Citizenship Behaviour, and job satisfaction have a simultaneous and significant effect on employee retention although work stress individually does not have a significant effect on employee retention. After trimming process, the result shows that Organizational Citizenship Behaviour and job satisfaction have a simultaneous and significant effect on employee retention. It means that if the company wants to maintain and improve employee retention, it must improve the Organizational Citizenship Behaviour through Job Satisfaction.